Antiproliferative activities of some 7-hydroxy-3-aryloxy-2-trifluoromethyl-4H-4-chromenone derivatives against 60 human cancer cell lines - Prykhod'ko, A.O.; Dubinina, G.G.; Khilya, V.P.; Yarmoluk, S.M. (Біополімери і клітина, 2004)
234 derivatives of 7-hydroxy-3-aryloxy-2-trifluoromethyl-4H-4-chromenones were synthesized and tested for antitumor activity in vitro against human cancer cell lines in NCI (National Cancer Institute, USA) bioassay. It was shown high cytostatic and cytotoxic activity for the tested compounds 1-8 (GI50 3.44-41.1 mM and LC50 from 49.6 mM). The relationship between structures of the tested compounds and their antiproliferative activities is discussed.